Simulation of Turbulent Flow and Heat Transfer in A double Tube Heat Exchanger with Twisted Tape (University of Thi-Qar Journal for Engineering Sciences, 2025)
Enhancing the thermal performance of a heat exchanger is a target for designers and researchers. This work uses numerical analysis to predict the thermal performance of a double-tube heat exchanger with a twist tape insert. Various twisting ratio (y/w) values of (2, 4, 6) were examined in the Re range of 5000 - 30000. The aim of this work is to assess the thermal performance of a double-tube heat exchanger by inserting a twisted tape. To model this physical issue, in addition to the turbulence model, the Navier-Stokes and energy equations are taken into account. ANSYS Fluent was adopted to simulate the model equations. The findings show that the twisted tape has a significant effect on the thermal performance of a heat exchanger.  An increased coefficient of overall heat transfer and efficiency was observed when the twisted tape was inserted into the tube. The effectiveness of the heat exchanger improved by 34% compared with the double tubes without tape.